Estágio Obrigatório Supervisionado na Secretaria Municipal de Meio Ambiente e Desenvolvimento Sustentável de São Carlos (SP) - Almeida, Leticia Kamimura (Universidade Federal de São Carlos, 2023)
This report aims to present the activities carried out during the mandatory internship supervised at the Municipal Council for the Defense of the Environment of São Carlos (COMDEMA) and at the Municipal Secretariat for the Environment and Sustainable Development, from November 2022 to January 2023. The activities were supervised by Elen Pilegi Neves, administrative assistant and executive secretary of COMDEMA, and Anna Paula Luzia, head of the environmental information section. Carrying out the internship enabled the intern to acquire experience in the area of public environmental management, through monitoring and participation in the activities of the São Carlos Municipal Council for the Defense of the Environment, assisting in the administrative organization and monitoring the discussion of topics relevant to the municipality, such as issuing favorable opinions to requests for environmental statements from companies; definition and establishment of standards, procedures; dissemination of activities and events promoted by public institutions and non-governmental organizations. This experience was fundamental for the intern to have the opportunity to participate in the routine of a Municipal Secretariat, experiencing and deepening the knowledge acquired during graduation. Highlighting the importance of the subjects offered by the Environmental Management and Analysis course, such as environmental planning, environmental education, public policies and the implementation of all interdisciplinary projects, which help in the formation of a systemic view of our environment, as well as the problems faced in management public, such as financing, lack of planning, decentralization and popular participation.
Mandatory Supervised Internship at the Municipal Department of Environment and Sustainable Development of São Carlos (SP)
Keywords: Gestão Ambiental; São Carlos; Secretaria Municipal de Meio Ambiente e Desenvolvimento Sustentável; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS SOCIAIS DO PLANEJAMENTO URBANO E REGIONAL